The application of Artificial Neural Networks (ANN) applications in various discipline of studies / Wan Nur Azah Wan Nahar and Rahimah Mohamed Yunos - Wan Nahar, Wan Nur Azah; Mohamed Yunos, Rahimah (Faculty of Accountancy, 2019)
Artificial Neural Networks (ANN) approaches are becoming useful as an alternate way to classical methods. As a computation and learning paradigm, they are presented as a different modeling approach to solve complicated problems. They have been used to solve complicated practical problems in various areas, such as accounting and business, engineering, medical and healthcare, geological and energy. They have also been applied for modeling, identification, prediction and forecasting. ANN have been extensively employed in numerous fields. They are not programmed in the conventional procedure but they are trained using data exemplifying the behavior of a system. This paper presents various applications of neural networks used in various studies. The applications of neural networks could be grouped in three major categories: (1) designing and modeling; (2) identification and evaluation and (3) prediction and control. Published literature presented in this study indicate the potential of ANN as a useful tool in various discipline for many industries. This paper will be very much useful to the researchers and professionals to find out the relevant references related to ANN and current studies related to it.